Essential SNMP - Mauro, Douglas R.
"This practical guide for network and system administrators introduces SNMP along with the technical background to use it effectively. But the main focus is on practical network administration: how to configure SNMP agents and network management stations, how to use SNMP to retrieve and modify variables on network devices, how to configure management software to react to traps sent by managed devices. Covers all SNMP versions through SNMPv3"
17598
102617
102618
15794
102620
10406
Keywords: REDES DE COMPUTADORES--ADMINISTRACION; REDES DE COMPUTADORES--ADMINISTRACION; SNMP (PROGRAMAS PARA COMPUTADOR)